Endoparasite community of Rattus norvegicus captured in a shantytown of Buenos Aires City, Argentina - Hancke, D. (2011)
Summary: The aim of this study was to evaluate the role of the brown rat (Rattus norvegicus) as a potential reservoir of zoonotic parasites in an urban area of Argentina. A parasitological survey in 40 brown rats trapped in a shantytown of Buenos Aires City was carried out. 97. 5 % of the analyzed rats were parasitized with at least one of the 12 species of helminth or protozoan species recorded. Among the species identified, Hymenolepis nana is recognized as one of the most common human helminthes parasites. The average number of parasite species was higher in males than females rats, and in the last case, a direct relationship between parasite species richness and host's body size was recorded. Variations in endoparasite community throughout the year seasons were recorded, probably related to environmental factors, which limits the performance of the life cycle of different parasite species. The presence of zoonotic endoparasites confirms R. norvegicus as a reservoir for different types of pathologies, which, therefore, represents a risk to the public health in an overcrowded urban area.